COMMUNICATIVE STRATEGIES AND TACTICS IN THE "INTERVIEW" SPEECH GENRE WHILE DISCUSSING MILITARY EVENTS IN UKRAINE BY THE GERMAN MEDIA - Nikolay A. Krasavsky (Izvestiâ Ûžnogo Federalʹnogo Universiteta: Filologičeskie Nauki, 2024)
The main communicative strategies and their implementing tactics were revealed in German newspaper interviews devoted to the events in Ukraine in March – May 2022. The main communication strategies in this genre of German media are the information and interpretation strategy, the strategy of the reader's emotional mood and the strategy of self-presentation. The most common lexical units, lexico-stylistic and syntactic-stylistic means that implement basic communicative tactics in interview texts are established.